Evidence for lysosomal biogenesis proteome defect and impaired autophagy in preeclampsia. Issue 10 (2nd October 2020) - Nakashima, Akitoshi; Cheng, Shi-Bin; Ikawa, Masahito; Yoshimori, Tamotsu; Huber, Warren J.; Menon, Ramkumar; Huang, Zheping; Fierce, Jamie; Padbury, James F.; Sadovsky, Yoel; Saito, Shigeru; Sharma, Surendra
ABSTRACT: The etiology of preeclampsia (PE), a serious pregnancy complication, remains an enigma. We have demonstrated that proteinopathy, a pathologic feature of neurodegenerative diseases, is a key observation in the placenta and serum from PE patients. We hypothesize that the macroautophagy/autophagy machinery that mediates degradation of aggregated proteins and damaged organelles is impaired in PE. Here, we show that TFEB (transcription factor EB), a master transcriptional regulator of lysosomal biogenesis, and its regulated proteins, LAMP1, LAMP2, and CTSD (cathepsin D), were dysregulated in the placenta from early and late onset PE deliveries. Primary human trophoblasts and immortalized extravillous trophoblasts (EVTs) showed reduced TFEB expression and nuclear translocation as well as lysosomal protein content in response to hypoxia. Hypoxia-exposed trophoblasts also showed decreased PPP3/calcineurin phosphatase activity and increased XPO1/CRM1 (exportin 1), events that inhibit TFEB nuclear translocation. These proteins were also dysregulated in the PE placenta. These results are supported by observed lysosomal ultrastructural defects with decreased number of autolysosomes in hypoxia-treated primary human trophoblasts. Autophagy-deficient human EVTs exhibited poor TFEB nuclear translocation, reduced lysosomal protein expression and function, and increased MTORC1 activity. Sera from PE patients induced these features and protein aggregation in EVTs. Importantly, trophoblast-specific conditional atg7 knockout mice exhibited reduced TFEB expression with increased deposition of protein aggregates in the placenta. These results provide compelling evidence for a regulatory link between accumulation of protein aggregates and TFEB-mediated impaired lysosomal biogenesis and autophagy in the placenta of PE patients. Abbreviation: atg7 : autophagy related 7; CTSD: cathepsin D; ER: endoplasmic reticulum; EVTs: extravillous trophoblasts; KRT7: keratin 7; LAMP1: lysosomal associated membrane protein 1; LAMP2: lysosomal associated membrane protein 2; mSt: mStrawberry; MTORC1: mechanistic target of rapamycin complex 1; NP: normal pregnancy; NPS: normal pregnancy serum; PE: preeclampsia; PES: preeclampsia serum; p-RPS6KB: phosphorylated ribosomal protein S6 kinase B1; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscopy; TFEB: transcription factor EB; XPO1/CRM1: exportin 1